POSSIBLE IMPACT OF THE ABE-KURO MONETARY EXPANSION ON THE INDONESIAN ECONOMY - Abimanyu, Yoopi (Jurnal Kajian Ekonomi dan Keuangan, 2013)
Abenomics, the economic policies of Japan, which recently has been changed into "Abe-Kuro" referring to the Prime Minister and the Governor of the Central Bank, consists of monetary policy, fiscal policy and growth package. It is meant to resolve Japan's low economic growth and deflation. This short note is trying to see the impact of one of the policies, which is the expansion monetary policy, on the Indonesian economy, in particular on the exchange rate and the balance of payments. The hypothesis of this note is that, even though the Indonesian exchange rate will be appreciated, the impact on the capital account is somewhat more significant relative to the current account. On the current account and capital account, the impact of the monetary expansion policy is more on the capital account, particularly the shortterm portfolio movement relative to the current account. Assuming that the United States will stop her monetary expansion policy, the Japan monetary expansion would substitute the United States policy. On the other hand, if the United States monetary expansion policy would be continued, then the Japan monetary expansion policy would supplement the United States policy. In both cases, the Rupiah exchange rate would be appreciated.Abenomics, the economic policies of Japan, which recently has been changed into "Abe-Kuro"referring to the Prime Minister and the Governor of the Central Bank, consists of monetary policy, fiscalpolicy and growth package. It is meant to resolve Japan's low economic growth and deflation. This shortnote is trying to see the impact of one of the policies, which is the expansion monetary policy, on theIndonesian economy, in particular on the exchange rate and the balance of payments. The hypothesis ofthis note is that, even though the Indonesian exchange rate will be appreciated, the impact on the capitalaccount is somewhat more significant relative to the current account. On the current account and capitalaccount, the impact of the monetary expansion policy is more on the capital account, particularly the shorttermportfolio movement relative to the current account. Assuming that the United States will stop hermonetary expansion policy, the Japan monetary expansion would substitute the United States policy. Onthe other hand, if the United States monetary expansion policy would be continued, then the Japanmonetary expansion policy would supplement the United States policy. In both cases, the Rupiah exchangerate would be appreciated.